The Lord is good: seeking the God of the Psalter - Holmes, Christopher R. J. (Studies in Christian Doctrine and Scripture, 2018)
Intro -- Acknowledgments -- Abbreviations -- Introduction -- Why Such a Book? -- ONE -- Simplicity -- TWO -- You Are Good -- THREE -- Goodness and the Trinity -- FOUR -- You Do Good -- FIVE -- The Good Creator -- SIX -- Goodness and Evil -- SEVEN -- Teach Me Your Statutes -- EIGHT -- Goodness and Jesus Christ -- NINE -- Perfection -- Conclusion -- Bibliography -- Notes -- Search items for authors and subjects -- Search items for ancient and biblical sources.